Applications of Multicomponent Reactions to the Synthesis of Diverse Heterocyclic Scaffolds - Sunderhaus, James D.; Martin, Stephen F. (Chemistry : a European journal, 2009)
The sequencing of multicomponent reactions (MCRs) and subsequent cyclization reactions is a powerful stratagem for the rapid synthesis of diverse heterocyclic scaffolds. The optimal MCR is sufficiently flexible that it can be employed to generate adducts bearing a variety of functional groups that may then be selectively paired to enable different cyclization manifolds, thereby leading to a diverse collection of products. The growing interest in diversity‐oriented synthesis has led to increased attention to this paradigm for library synthesis, which has inspired many advances in the design and implementation of MCRs for the construction of diverse heterocyclic scaffolds. So much from so little! The sequencing of multicomponent reactions (MCRs) with subsequent cyclization reactions is a powerful method for generating diverse collections of functionalized heterocyclic scaffolds (see scheme).